Age estimation by ossification of thyroid cartilage of Japanese males using Bayesian analysis of postmortem CT images. (March 2017) - Aramaki, Tomomi; Ikeda, Tomoya; Usui, Akihito; Funayama, Masato
Highlights: There are individual differences in age-related thyroid cartilage ossification. A scoring system was introduced to verify age using Bayesian statistics. Using an estimation table in 39 male, two individuals were inaccurately scored. Bayesian statistics of thyroid cartilage ossification may work in age estimation. Abstract: Many studies have reported that the degree of thyroid cartilage ossification correlates with age. However, its use in forensics has been limited by individual variation, tissue fragility, and observer subjectivity. We examined a new method for age estimation from the degree of ossification of thyroid cartilage using postmortem computed tomography (CT) and Bayesian analysis. The scoring of CT density values, ossification rate, and morphological changes was performed in 131 Japanese males (20–80 years old), and an age estimation table was created and verified in 39 other Japanese males. We tried two types of prior probability; one was males undergoing postmortem CT imaging at our institute, and the other was the age composition of the male population in Japan. The differences in percentage in each age group were observed, especially in the ninth decade, but they were not large enough to change the result. Two decedents in their 30s and 80s could not be assigned an age group. Likelihood might have had more significant influence than prior probability. Bayesian approach and new scoring system of thyroid cartilage ossification might be useful as an age estimation method. Although the low posterior probability in decedents the age ≧70 remains a problem, the advantage of Bayesian estimation that it can sequentially update the age estimation table by factoring in exceptional data can solve this problem. In this study, accuracy of age estimation did not dramatically increase, however, Bayesian statistics might become a useful technique for examining any tissue samples subject to age-related calcification.